Kultura korporacji w perspektywie nowej ekonomii instytucjonalnej - Klimczak , Bożena (Człowiek i Społeczeństwo, 2014)
The aim of this article is to approach the roots of the corporate culture in the light of New Institutional Economics. The basis of analysis is the concept of four levels of the institutions by O.E. Williamson. The corporate governance is embedded in tradition (level 1) and in formal institutions (level 2). In European civilization tradition means especially – religion, so the American and European corporations culture is connected with religious Christian values. In the first part of the article the traditional, religion embeddedness of economic culture (level 1) is discussed. In the second part of the article two institutional theories of corporate governance (level 3) are discussed: agency theory and transactions costs theory. The connection between level 3 and level 1 as the roots of corporate governance is the transactions cost theory. In the summary the integration between corporate governance and corporate social responsibility is shown.